ETHNOBOTANY Melaleuca cajuputi (sub-species cumingiana) BETWEEN THE SABUHUR RIVER AS A POPULAR SCIENTIFIC BOOK - Fitriyani Fitriyani; Dharmono Dharmono; Maulana Khalid Riefani (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Ethnobotany Galam (Melaleuca cajuputi, subspecies cumingiana) on the bank of Sabuhur river still not available yet in Ethnobotany course. Learning product based on local content are expected to add insight to the use of local plant. Material related to regional potential are specials, that are adapted to local situation. Galam has many benefits, which is learning support material. This study aims to describe the Ethnobotany of Galam on the bank of Sabuhur river and validity of popular scientific books. This research is descriptive research and formative evaluation of the Tessmer test. Based on expert judgment, the book has an average score of 87.5% and is included at very valid category. The popular scientific book has procedural and theoretical feasibility.